Introduction - Franke, Katherine (Columbia Journal of Gender and Law, 2010)
Each year, the Center for Gender & Sexuality Law devotes a day- long symposium to the significant contributions of a senior scholar to the literature of gender and/or sexuality law and theory. For our inaugural symposium we were pleased to have selected Martha Nussbaum, the Ernst Freund Distinguished Service Professor of Law and Ethics at the University of Chicago with joint appointments in the Philosophy Department, Law School and Divinity School. Professor Nussbaum’s work spans a daunting terrain. In her work as a classicist and theorist of liberal humanism, she has both explored an ethics of vulnerability and human flourishing, in The Fragility of Goodness (1996), and defended liberal education in Cultivating Humanity (1997). In Hiding from Humanity (2004) she used tools from moral psychology to better understand the role that shame and disgust play in legal argument, focusing in particular on the subordination of women, Jews and homosexuals. Her Sex and Social Justice (1999) defended a universal notion of gendered and sexuality-based justice that demonstrates the ineluctable link between sex and social justice. Finally, in Women and Human Development (2000) and Frontier of Justice (2006) she made a compelling case for defining development goals in terms of human capabilities that insist on the priority of gender and sex-based justice.